EFEKTIVITAS DAN EFEK SAMPING PENGGUNAAN IUD PASCA PLASENTA DI RSPAL DR. RAMELAN PERIODE JANUARI 2019 – DESEMBER 2021 - Suroso, Anisha Farah (Fakultas Kedokteran, Universitas Hang Tuah, 2023)
Background : In 2020 Indonesia has experienced an increase in population which has become a problem in Indonesia. In preventing the population explosion, the government established a program, named Family Planning (KB). In the family planning program, there is a contraceptive method, named the Intra Uterine Device (IUD). Post-placental IUD contraception is a safe, easy dan effective contraceptive for inserting a long-term intrauterine contraceptive device (IUD) with convenience in use, dan ease dan lower side effects. Study aims : To determine the effectiveness dan side effects of using a post-placental IUD at Dr Ramelan Hospital for the period January 2019 – December 2021. Methods : The research design was a descriptive research design using quantitative methods. Researchers used secondary data in the form of electronic medical records (SIMRS) with a total sample of 88 people. The data examined included age, parity, duration of use of the post-placental IUD, the effectiveness of the post-placental IUD, the side effects of the post-placental IUD such as: pain, menstrual disorders, bleeding, dan IUD removal. Results : From a total sample of 88 people, the effectiveness of the post-placental IUD was 96.6%, dan the side effects that occurred were frequent pain in 26 people (29.5%), menstrual disorders in 33 people (37.5%) ), bleeding disorders in 21 people (23.9%), dan removing the IUD in 31 people (35.2%). Conclusion : The effectiveness of the post-placental IUD is 96.6%, dan the side effects that occur during post-placental IUD users are pain, menstrual disorders, bleeding, dan IUD removal.